2019
DOI: 10.7554/elife.45222
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanisms of phospholipid activation of the human TPC2 channel

Abstract: Mammalian two-pore channels (TPCs) regulate the physiological functions of the endolysosome. Here we present cryo-EM structures of human TPC2 (HsTPC2), a phosphatidylinositol 3,5-bisphosphate (PI(3,5)P2)-activated, Na+ selective channel, in the ligand-bound and apo states. The apo structure captures the closed conformation, while the ligand-bound form features the channel in both open and closed conformations. Combined with functional analysis, these structures provide insights into the mechanism of PI(3,5)P2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 45 publications
6
145
2
Order By: Relevance
“…Because TPC2 is a PI-dependent and non–voltage-dependent channel ( Wang et al, 2012 ), PI binding needs to provide the energy sufficient to open the gate without any contribution from VSDs. Very recently solved cryo-EM structures of human TPC2 in the apo- and PI(3,5)P 2 -bound states reveal that the distance between those residues decreases in the PI(3,5)P 2 -bound state ( She et al, 2019 ). The tight IS6–IIS6 interaction identified in this study might contribute to enabling movement of both IS6 and IIS6, so that gate opening in TPC2 occurs in response to PI binding alone.…”
Section: Discussionmentioning
confidence: 99%
“…Because TPC2 is a PI-dependent and non–voltage-dependent channel ( Wang et al, 2012 ), PI binding needs to provide the energy sufficient to open the gate without any contribution from VSDs. Very recently solved cryo-EM structures of human TPC2 in the apo- and PI(3,5)P 2 -bound states reveal that the distance between those residues decreases in the PI(3,5)P 2 -bound state ( She et al, 2019 ). The tight IS6–IIS6 interaction identified in this study might contribute to enabling movement of both IS6 and IIS6, so that gate opening in TPC2 occurs in response to PI binding alone.…”
Section: Discussionmentioning
confidence: 99%
“…TM5 and TM6 from each set of protomers assemble to form a central ion conduction pore [105]. Unlike TPC1 and TPC3, TPC2 functions as a voltage-independent cation channel, meaning that the channel is opened in response only to the binding of its ligands, independently from membrane potential [105][106][107]. The opened channel allows the cation (Na + or Ca 2+ ) to flow across from lumen to cytosol (cation conductance).…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%
“…NAADP-sensing TPC2 mediates Ca 2+ release in lysosome and endolysosome [58,59,[110][111][112][113][114]. PI(3,5)P 2 -dependent TPC activation induces Na + release [105,[115][116][117][118]. Despite the difference of stimuli and responsive ions, most studies demonstrate the common role of TPC2 in lysosomal Structural model of human SLC24A5 is predicted based on the structure of archaebacterial ortholog NCX_Mj; left, side view; right, top view.…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%
“…However, a recent study provided information that human TPC is, in fact, not directly activated by NAADP [ 96 ]. Although the 3D structures of mouse TPC1 and human TPC2 were recently determined by cryo-EM [ 97 , 98 ], the bound state of NAADP on these channels remains unknown, and further investigation is still required. There are also a series of studies developing a photoaffinity probe for the NAADP receptor, 5-N 3 -NAADP, which showed that NAADP did not bind to TPCs directly, but through NAADP-binding proteins [ 99 ].…”
Section: Two-pore Channels (Tpcs)mentioning
confidence: 99%